PENGARUH PERSEPSI KEGUNAAN DAN PERSEPSI KEMUDAHAN TERHADAP NIAT BELI DENGAN SIKAP SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Pengguna Traveloka) - Nur Islami, Rahmi; Syahran; Lestari, Putri Indah (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim : This research aims to test the influence of perceived usefulness and perceived convenience on purchase intention with attitude as a mediating variable. This research was conducted in Tarakan City. Design/Methode/Approach : The theoretical approach used in this research is the Technology Acceptance Model (TAM). This research uses a survey method with an instrument in the form of a questionnaire and a sampling method using nonprobability sampling. The validity test uses convergent validity and discriminant validity, and the reliability test uses composite reliability. Research Finding : The results of this research indicate that the variables of perceived usefulness and convenience have a positive and significant effect on the attitude variable. The attitude variable has a positive and significant effect on purchase intention. Theoretical contribution/Originality : This study strengthens the empirical foundation of the Technology Acceptance Model (TAM) by validating the mediating role of attitude in explaining consumer purchase intention within the digital transaction context in Indonesia. Practitionel/Policy implication : The findings provide insights for marketers and digital business practitioners to enhance user perceptions of usefulness and convenience to improve consumer attitudes and ultimately increase purchase intentions. Research limitation : This research was limited to respondents in Tarakan City; future studies are suggested to include larger samples and cross-regional comparisons to improve generalizability.